Reproductive isolation between two populations of Aglaoctenus lagotis , a funnel-web wolf spider - González Pérez, María de la Macarena (2015)
Aglaoctenus lagotis (Lycosidae: Sosippinae) is a spider that, in contrast to the predominant wandering habit of the family, constructs funnel webs. The species is widely distributed throughout the Neotropics and is credited with high levels of intraspecific variation. Here, we evaluate whether reproductive isolating barriers operate between some populations of A. lagotis. We used heterotypic encounters between individuals from two distant localities: southern Uruguay (SU) and Central Argentina (CA). Additionally, we used spiders from an ntermediate locality, western Uruguay (WU), where both forms of the species overlap (SU.WU was used to describe individuals from WU reminiscent of those from SU; and CA.WU was used to describe individuals from WU reminiscent of those from CA). No copulations occurred between SU and CA individuals, whereas a single and atypical copulation occurred between SU.WU and CA.WU individuals. Attacks (only by females on males) were rare. In tests of choice based on silk cues, SU males did not prefer homotypic cues but almost did not court CA females, whereas CA males preferred homotypic cues but usually courted heterotypic females. These findings, with a previously reported temporal asynchrony between populations, suggest the occurrence of reproductive isolation between both spider forms and a speciation process favoured by the wide distribution and plasticity of the species.